ACL prevention in female handball - Myklebust, G. (ASPETAR Sports Medicine Journal, 2014)
Knowledge regarding ACL injuries in handball has improved substantially in the last 10 to 15 years. We know more about who is injured, how the injury happens and most importantly, how ACL injuries can be prevented. We now know that female players can reduce their risk of an ACL injury by 50%! This is the most important message in the following paper, which will describe how players can achieve this 50% reduction and why it is important, as well as who is at risk of injury.